National games for local gains: legislative activity, party organization and candidate selection. Issue 1 (2nd January 2020) - Chiru, Mihail; Gherghina, Sergiu
ABSTRACT: Conventional research on political careers has emphasized the use of local offices as a springboard for national careers. However, movements in the reverse direction can also happen when local offices are available and attractive for national level politicians. This article argues that various types of legislative behavior and party strategy influence the likelihood that national legislators run in local elections and tests how this happens. The analysis focuses on Romania and uses an original dataset compiled for the 2016 local elections. Our findings show that legislators with a rich record of parliamentary activity will continue at the national level, while those who do constituency work, and those who can help their parties more locally, move to local politics.